Synthesis, DFT study, molecular docking and drug-likeness analysis of the heteroaryl substituted new pregnenolone derivatives - Capan, Irfan; Sert, Yusuf; Shehu, Abdulmalik; Koca, Irfan; Servi, Suleyman (Elsevier, 2022)
The hybrid molecules having heterocyclic structures in the D-ring of steroids have significant biologi -cal activities. Pregnenolone was converted to the hetero-arylidene derivatives by the aldol condensa-tion reaction with two different heteroaromatic aldehydes in the alkali medium. New N -thiocarbomyl and N-acetyl substituted non-fused pyrazoline derivatives were synthesized from the reaction of the re-sulting hetero-arylidene steroid derivatives with thiosemicarbazide and hydrazine hydrate, respectively, in different reaction conditions. Also, the endocyclic double bond of the 2-pyridinyl substituted hetero-arylidene molecule was converted with stereo-and regioselective dihydroxylation reaction to the new trans-diaxial diol derivative. The theoretical binding affinities of nine compounds with human microsomal cytochrome protein P450 (CYP17; PDB: 1RUK) were evaluated using molecular docking simulations with the AutoDockVina program, and the obtained scores were compared lengthily in the relevant section. Ad-ditionally, ADME and drug-likeness analysis were performed for newly synthesized steroids. Finally, using the theoretical MEP analysis over the optimized structures, electrophilic and nucleophilic attack sites of the steroids were clearly determined and evaluated.(c) 2022 Elsevier B.V. All rights reserved.
Keywords: Pregnenolone; Hetero-arylidene; Pyrazoline; Carbothioamide; Trihydroxy sterol; ADMET analysis